Analytical and Approximate Solutions for Complex Nonlinear Schrdinger Equation via Generalized Auxiliary Equation and Numerical Schemes - Khater, Mostafa M. A.; Lu, Dian-Chen; Attia, Raghda A. M.; İnç, Mustafa (Iop Publishing Ltd, 2019)
This article studies the performance of analytical, semi-analytical and numerical scheme on the complex nonlinear Schrdinger (NLS) equation. The generalized auxiliary equation method is surveyed to get the explicit wave solutions that are used to examine the semi-analytical and numerical solutions that are obtained by the Adomian decomposition method, and B-spline schemes (cubic, quantic, and septic). The complex NLS equation relates to many physical phenomena in different branches of science like a quantum state, fiber optics, and water waves. It describes the evolution of slowly varying packets of quasi-monochromatic waves, wave propagation, and the envelope of modulated wave groups, respectively. Moreover, it relates to Bose-Einstein condensates which is a state of matter of a dilute gas of bosons cooled to temperatures very close to absolute zero. Some of the obtained solutions are studied under specific conditions on the parameters to constitute and study the dynamical behavior of this model in two and three-dimensional.
Keywords: complex NLS equation; generalized auxiliary equation method; adomian decomposition method; B-splines schemes (cubic & quintic & septic)